The Legal Reform Policy on the Shariah Supervisory Board Role’s in Indonesian Shariah Banks - Devi Triasari; Francesco de Zwart (BESTUUR, 2021)
As Muslim majority country, Indonesia experiences the mushrooming of banks based on Islamic values (called shariah banking). The existence of sharia banking is followed by legal policies intended to support the progress of the business sector, including regulations regarding the Sharia Advisory Board, but the question is whether the policy is effective in the development of sharia banking in Indonesia. Adherent to that context, this study aims to examine the issues faced by the Sharia Supervisory Board in Indonesia. This study argues that there are at least fifth substantial problems related to the policies of the Sharia Supervisory Board in Indonesia, namely: (1) not all Shariah Supervisory Boards in Islamic business units have supported by a strong legal basis on which their operations are inducted to; (2) members of the Shariah Supervisory Board are appointed mostly based on their charisma and popularity in society, not of their knowledge and experience in related field; (3) ideally Shariah Supervisory Board must have recognized the banking system before becoming Shariah Supervisory Board, but the basic knowledge is not easy to understand when entering on technical issues; (4) many Shariah Supervisory Boards are not focused on shariah banks supervision duty because of their multi profession; (5) lack of advice related to product innovation and social needs issues.